What Factors Stimulate Impulse Buying in Live Commerce? - Made Pradnyan Permana Usadi; I Putu Wahyu Dwinata JS; I Wayan Sucipta Wibawa (E-Mabis: Jurnal Ekonomi Manajemen dan Bisnis, 2023)
The emergence of live streaming commerce has become evidence that the e-commerce has developed rapidly since Covid-19 pandemic. Consumers who shop at live commerce mostly don’t have a previous plan. This behavior is certainly influenced by various stimuli created by sellers. This study aims to investigate factors in stimulating purchase decisions. The sample used is 100 respondents. Data analysis used is Partial Least Square. The results indicate that interactivity has a significant effect on arousal, and leads to impulse buying. Attractiveness and perceived scarcity have no effect on arousal. This study implies that sellers should focus on improving the way they communicate with consumers. Hence, consumers can feel the togetherness and intimacy and enable impulse purchase to occur.